Severe Acute Respiratory Syndrome Coronavirus 2 Convalescent Plasma Versus Standard Plasma in Coronavirus Disease 2019 Infected Hospitalized Patients in New York: A Double-Blind Randomized Trial*. Issue 7 (19th April 2021) - Bennett-Guerrero, Elliott; Romeiser, Jamie L.; Talbot, Lillian R.; Ahmed, Tahmeena; Mamone, Linda J.; Singh, Sunitha M.; Hearing, Janet C.; Salman, Huda; Holiprosad, Dishaw D.; Freedenberg, Alex T.; Carter, Jason A.; Browne, Nicholas J.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: Four peer-reviewed publications have reported results from randomized controlled trials of convalescent plasma for coronavirus disease 2019 infection; none were conducted in the United States nor used standard plasma as a comparator. To determine if administration of convalescent plasma to patients with coronavirus disease 2019 increases antibodies to severe acute respiratory syndrome coronavirus 2 and improves outcome. DESIGN: Double-blind randomized controlled trial. SETTING: Hospital in New York. PATIENTS: Patients with polymerase chain reaction documented coronavirus disease 2019 infection. INTERVENTIONS: Patients were randomized (4:1) to receive 2 U of convalescent plasma versus standard plasma. Antibodies to severe acute respiratory syndrome coronavirus 2 were measured in plasma units and in trial recipients. MEASUREMENTS AND MAIN RESULTS: Enrollment was terminated after emergency use authorization was granted for convalescent plasma. Seventy-four patients were randomized. At baseline, mean (sd ) Acute Physiology and Chronic Health Evaluation II score (23.4 [5.6] and 22.5 [6.6]), percent of patients intubated (19% and 20%), and median (interquartile range) days from symptom onset to randomization of 9 (6–18) and 9 (6–15), were similar in the convalescent plasma versus standard plasma arms, respectively. Convalescent plasma had high neutralizing activity (median [interquartile range] titer 1:526 [1:359–1:786]) and its administration increased antibodies to severe acute respiratory syndrome coronavirus 2 by 14.4%, whereas standard plasma administration led to an 8.6% decrease ( p = 0.005). No difference was observed for ventilator-free days through 28 days (primary study endpoint): median (interquartile range) of 28 (2–28) versus 28 (0–28; p = 0.86) for the convalescent plasma and standard plasma groups, respectively. A greater than or equal to 2 point improvement in the World Health Organization scale was achieved by 20% of subjects in both arms ( p = 0.99). All-cause mortality through 90 days was numerically lower in the convalescent plasma versus standard plasma groups (27% vs 33%; p = 0.63) but did not achieve statistical significance. A key prespecified subgroup analysis of time to death in patients who were intubated at baseline was statistically significant; however, sample size numbers were small. CONCLUSIONS: Administration of convalescent plasma to hospitalized patients with coronavirus disease 2019 infection increased antibodies to severe acute respiratory syndrome coronavirus disease 2 but was not associated with improved outcome.